2010
DOI: 10.1152/ajplung.00002.2009
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits fibrosis-related effects in IPF fibroblasts and in mice following bleomycin-induced lung injury

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive and typically fatal lung disease for which no effective therapy has been identified. The disease is characterized by excessive collagen deposition, possibly in response to dysregulated wound healing. Mediators normally involved in would healing induce proliferation of fibroblasts and their differentiation to myofibroblasts that actively secrete collagen. Curcumin, a polyphenolic compound from turmeric, has been shown to exert a variety of biological effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
85
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 42 publications
7
85
0
Order By: Relevance
“…The dose of curcumin used by us was based on its optimal anti-TGF-␤ effects at 5 mg/kg body wt in our preliminary experiments with 2.5, 5, and 20 mg/kg body wt. This dose is markedly lower than those used in adults by others, either by the oral or parenteral route (10,29). Our investigation into the mechanism of curcumin's protective effect on neonatal lung injury suggests blockage of hyperoxia-induced oxidative stress and TGF-␤ activation.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The dose of curcumin used by us was based on its optimal anti-TGF-␤ effects at 5 mg/kg body wt in our preliminary experiments with 2.5, 5, and 20 mg/kg body wt. This dose is markedly lower than those used in adults by others, either by the oral or parenteral route (10,29). Our investigation into the mechanism of curcumin's protective effect on neonatal lung injury suggests blockage of hyperoxia-induced oxidative stress and TGF-␤ activation.…”
Section: Discussionmentioning
confidence: 64%
“…However, it is important to point out that a number of studies have stressed the limited bioavailability of oral curcumin, thereby necessitating parenteral administration to achieve its effects (13,27,29). Therefore, we opted for the intraperitoneal route over the oral route for its administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the reports pay more attention to the anti-fibrosis activity of curcumin on TGF-β1-stimulated organs (Tubulointerstitial, corneal, liver, etc.) fibrosis via blocking TGF-β signing pathway (Smith et al, 2010;Yao et al, 2012;Zhang et al, 2012). Kim et al have confirmed that curcumin inhibites TGF-β1-induced MMPs in mouse keratinocytes (Santibáñez et al, 2000;Santibáñez et al, 2002), but the effects on breast cancer MDA-MB -231 have not been reported.…”
Section: Introductionmentioning
confidence: 97%
“…Studies of human gingival fibroblasts, lung fibroblasts, hepatic stellate cells, synoviocytes and cell lines from various malignant tumors demonstrated that curcumin inhibits cell proliferation and induces apoptosis (Jiang et al, 1996;Atsumi et al, 2006;Chen et al, 2006;Divya and Pillai, 2006;Jackson et al, 2006;Lin et al, 2009;Montopoli et al, 2009;Smith et al, 2010;Wu et al, 2010;Liu et al, 2011). The mechanisms implicated in curcumin-induced apoptosis appear to be DOI:http://dx.doi.org/10.7314/APJCP.2012.13.1.289 Antifibrotic Effect of Curcumin in TGF-β1-Induced Myofibroblasts from Human Oral Mucosa multifactorial, including effect on the stability of p53, the release of cytochrome c from mitochondria, and the generation of ROS (Strimpakos and Sharma, 2008).…”
Section: Discussionmentioning
confidence: 99%